Partisanship, globalization, and Canadian labour market policy : four provinces in comparative perspective - Haddow, Rodney (Studies in comparative political economy and public policy., 2006)
"Globalization is widely believed to have restricted the freedom of policy-makers in developed capitalist nations. In effect the forces of a global economy often prevent different political parties, governments, and the electorate from making distinct and meaningful policy choices. In Partisanship, Globalization, and Canadian Labour Market Policy, Rodney Haddow and Thomas Klassen explore the implications of this issue by comparing labour market policy in Canada's most populous provinces - Ontario, Quebec, British Columbia, and Alberta - between 1990 and 2003." "Drawing on a range of theoretical approaches, source materials, and in-depth case studies, the colume provides insights and perspectives on labour market policy in Canada, and also on wider issues of partisanship, globalization, and governance."--Jacket